Teachers’ Instructional Strategies in Addressing Learning Loss in Post-Pandemic Education - Muhammad Nurfaizi Arya Rahardja; Moh. Imron Rosidi; Rafeah Husni; Elinda Novita Dewi (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigates teachers’ instructional strategies for addressing learning loss in post-pandemic secondary education through a qualitative descriptive multiple-site design. Data were collected via semi-structured interviews, non-participant classroom observations, and document analysis of lesson plans, assessment records, and remedial guidelines, enabling triangulation between teachers’ rationales, enacted practices, and institutional expectations. Thematic analysis identified three interrelated strategy clusters shaping learning recovery. First, teachers employed diagnostic-driven instruction to map heterogeneous learning gaps and implement targeted remediation, strengthening precision in support allocation. Second, technology-enabled, blended, and adaptive instruction functioned as a recovery infrastructure that expanded differentiation, feedback cycles, and continuity of learning beyond classroom time. Third, sustainable recovery depended on professional collaboration, socio-emotional re-engagement, and family partnerships that rebuilt motivation, classroom stability, and shared responsibility for progress. Findings indicate that learning loss operates as a multidimensional challenge influenced by structural disparities and accountability pressures, requiring integrated pedagogical responses rather than isolated interventions. The study contributes evidence-based implications for recovery-oriented teaching and policy frameworks that support responsive instruction, teacher capacity building, and equitable post-pandemic learning restoration.